1988
DOI: 10.1530/jrf.0.0840653
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian capillary blood flow in seasonally anoestrous ewes induced to ovulate by treatment with GnRH

Abstract: Summary. The In the ewes exhibiting normal luteal function, the mean ovarian capillary blood flow was significantly greater (P < 0\m=.\01) than that for ewes having abnormal luteal function. Irrespective of the type of CL produced, capillary blood flow was significantly greater (P < 0\m=.\05) in ovulatory ovaries than in non-ovulatory ovaries.These findings indicate that the rate of capillary blood flow in ovaries near ovulation may be a critical factor in normal development and maturation of preovulatory fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
1997
1997

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Hence, inhibitory effects on ovulation induced by the use of NOS inhibitors may be due to inhibition of NO-derived relaxation of ovarian vascular smooth muscle and unmasking of the vasopressor response to endothelin [35], leading to decreases in ovarian blood flow or, in the case of the in vitro-perfused ovaries, decreases in perfusate flow. Ovarian blood flow normally increases as ovulation approaches [36,371 and contributes to the hyperemia and macroscopically observable "follicular blushing" that accompany the general increase in vascular permeability and edema observed in ovulating ovaries. By comparing the flow rates of LH-perfused and LH + L-NAME-perfused ovaries we have shown that there is an approximately 46% decrease in flow rate upon addition of the NOS inhibitor at a dose of 3.5 X 10 -5 mol/L; as mimicked in optimally stimulated ovaries, this resulted in a decreased ovulation rate that accounted for approximately 76% of the effect observed in this group when perfused with L-NAME.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, inhibitory effects on ovulation induced by the use of NOS inhibitors may be due to inhibition of NO-derived relaxation of ovarian vascular smooth muscle and unmasking of the vasopressor response to endothelin [35], leading to decreases in ovarian blood flow or, in the case of the in vitro-perfused ovaries, decreases in perfusate flow. Ovarian blood flow normally increases as ovulation approaches [36,371 and contributes to the hyperemia and macroscopically observable "follicular blushing" that accompany the general increase in vascular permeability and edema observed in ovulating ovaries. By comparing the flow rates of LH-perfused and LH + L-NAME-perfused ovaries we have shown that there is an approximately 46% decrease in flow rate upon addition of the NOS inhibitor at a dose of 3.5 X 10 -5 mol/L; as mimicked in optimally stimulated ovaries, this resulted in a decreased ovulation rate that accounted for approximately 76% of the effect observed in this group when perfused with L-NAME.…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone may act on the hypothalamic-pituitary pathway (Martin et al, 1983), or at the level of the ovary (Hunter et al, 1986;Brown et al, 1988) or uterus. This latter suggestion has been widely studied (Vallet et al, 1990).…”
Section: Introductionmentioning
confidence: 99%